Strategi Guru dalam Mengatasi Siswa yang Kurang Aktif di Kelas - Ridho Riskitullah; Lathifah Azzahra; Veli Fitriani (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2025)
Low student engagement in classroom activities remains a common challenge for teachers. This study aims to examine the strategis implemented by elementary school teachers to address student inactivity. A descriptive qualitative approach was employed, using interviews and classroom observations involving five teachers in padang, Indonesia. The findings revealed four primary strategies, cooperative learning, differentiated instruction, positive reinforcement, and the integration of interactive media and technology. These startegis were found to enhance students cognitive and social participation. The result highlight the essential role of teachers in designing adaptive learning startegies that align with student characteristics. This study recommends strengthening that align eith student characteristics. This study recommends strengthening teacher capacity through countinous and reflective teaching practices to support active and inclusive learning environments.